Studies on Lymph Node Dissection in Nerve-preserving Surgery for Rectal Canser Using a CUSA - Akatsuka, S.; Kubouchi, K.; Katagiri, M.; Sadahiro, S.; Omura, T.; Yamada, Y.; Tsumura, O.; Kodaira, S. (Nippon Daicho Komonbyo Gakkai Zasshi, 1987)
Lymph node dissection was performed in nerve-preserving surgery for rectal cancer using a Cavitron Ultrasonic Surgical Aspirator (CUSA). First, the preaortic plexus, superior hypogastric plexus, and hypogastric nerves were preserved using the CUSA, and separated lymph nodes were dissected out using scissors. The preserved plexus and nerves were then removed with scissors and examined for any remaining lymph nodes. The above procedure was performed on eight patients with rectal cancer, and it was found that 9, 6, 5, 4, 2, 0, 0 and 0 lymph nodes were left, respectively. The above observations suggest that lymph node dissection by CUSA does not yield perfect results.